Case report: Novel ETFDH compound heterozygous mutations identified in a patient with late-onset glutaric aciduria type II - Zhu, Sijia; Ding, Dongxue; Jiang, Jianhua; Liu, Meirong; Yu, Liqiang; Fang, Qi (Frontiers in Neurology, 2023)
Glutaric aciduria type II (GA II) is an autosomal recessive metabolic disorder of fatty acid, amino acid, and choline metabolism. The late-onset form of this disorder is caused by a defect in the mitochondrial electron transfer flavoprotein dehydrogenase or the electron transfer flavoprotein dehydrogenase (ETFDH) gene. Thus far, the high clinical heterogeneity of late-onset GA II has brought a great challenge for its diagnosis. In this study, we reported a 21-year-old Chinese man with muscle weakness, vomiting, and severe pain. Muscle biopsy revealed myopathological patterns of lipid storage myopathy, and urine organic acid analyses showed a slight increase in glycolic acid. All the aforementioned results were consistent with GA II. Whole-exome sequencing (WES), followed by bioinformatics and structural analyses, revealed two compound heterozygous missense mutations: c.1034A > G (p.H345R) on exon 9 and c.1448C>A (p.P483Q) on exon 11, which were classified as “likely pathogenic” according to American College of Medical Genetics and Genomics (ACMG). In conclusion, this study described the phenotype and genotype of a patient with late-onset GA II. The two novel mutations in ETFDH were found in this case, which further expands the list of mutations found in patients with GA II. Because of the treatability of this disease, GA II should be considered in all patients with muscular symptoms and acute metabolism decompensation such as hypoglycemia and acidosis.